A Worldwide Phylogenetic Analysis of Scutellaria (Lamiaceae) - Mercer, Elizabeth D. (2013)
The plant genus Scutellaria L. (Lamiaceae) is comprised of approximately 350 cosmopolitan species. Twenty-four species are found in the southeastern United States. The genus has been used medicinally on multiple continents, predominantly for its anxiolytic, anti-inflammatory and analgesic properties. Recently, certain species in the genus have been investigated for their ability to inhibit cancer cell growth. Despite the vast interest in the group, a molecular phylogeny has never been performed on the genus as a whole. My project involves a preliminary phylogenetic analysis of Scutellaria with representatives from every continent except Antarctica. DNA from field, herbaria (MO, NY, VSC) and lab specimens were extracted for a total of 30 species including one outgroup taxon, Holmskioldia sangunea. Gene regions sequenced include matK and the trnL intron + trnL-F spacer. The resulting phylogeny will provide preliminary scaffolding upon which a more targeted approach to medicinal screening within the genus can be based. Catherine Bush; Richard Carter; John Elder; Gil Nelson;